Latent organizing for responding to emergencies: Foundations for research - Paul C.cvan Fenema; A. Georges L. Romme (Journal of Organization Design, 2020)
Time and again, many organizations and their staff members must respond to unexpected catastrophes like hurricanes (e.g., Katrina), virus pandemics (e.g., COVID-19), or other major emergencies. As a result, some organizations allow their employees to respond to external emergencies by engaging in response actions for a limited time, like in the case of emergency response teams. The latter teams consist of employees that act as emergency response officers who can respond to floods, train crashes, or other emergencies. Emergency response teams constitute an example of so-called latent organizing (LO) in the preparation for and response to any (unpredictable) future emergency. While latent organizing is ubiquitous in a societal and professional sense, it has hardly been studied in the organization design literature. In this paper, we develop a research agenda for studying LO. LO serves to prepare for and respond to emergencies, but otherwise remains largely dormant and inactive. When it is inactive, host organizations use the LO's human and other resources for their own gainful purposes. Resources for LO are thus organized in a quasi-permanent fashion, one that is rather latent until activated by an emergency. We further develop the construct of latency to explore how effective LO can be designed and facilitated. In addition, we develop a research agenda for future work in this area.
Keywords: 650; Organization design; Latent organizing; Resource management; Capability; Routines; Emergency response; Catastrophes